Development of a kinetic model for Fischer-Tropsch synthesis over a Ru promoted Co/Al2O3 catalyst in a slurry reactor - Bhatelia, Tejas; Ma, W.; Jacobs, G.; Davis, B.; Bukur, D. (2011)
Depleting oil reserves, environmental pressure, as well as abundant reserves of coal, natural gas and biomass, have all contributed to a revived interest in Fischer-Tropsch (F-T) technology for producing ultra-clean, virtually sulfur-free, transportation fuels and chemicals. F-T technology involves conversion of synthesis gas (i.e., a mixture of H 2 and CO) to hydrocarbons, which can be upgraded by processes such as hydrocracking to produce liquid transportation fuels and chemicals - especially diesel, jet fuels, lubricants and waxes. F-T synthesis is a very complex reaction that produces a large number of products. The reaction is catalyzed by certain metals or metal carbides of the transition metal elements Co, Ru, Ni, and Ru (Dry, 1996). Due to the low intrinsic water-gas-shift activity of Co and the fact that it is easier to separate from the products than Fe based catalysts, cobalt based catalysts are used in commercial reactors for gas-to-liquids (GTL) conversion.